Hubungan Nilai Fraksi Ejeksi Ventrikel Kiri Dengan Tingkat Gejala Ansietas Yang Diukur Menggunakan Beck Anxiety Inventory (BAI) Pada Pasien Gagal Jantung - Adinda Nadira Larasati; Faisal Habib (JURNAL PANDU HUSADA, 2020)
Abstract: Heart failure is a progressive health problem with high mortality and morbidityin developed and developing countries including Indonesia. Heart failure can lead tochronic physical disability, which is a high economic burden. Chronic diseases, especially diseases that greatly affect functional abilities such as heart failure are associated with physical, psychological, and lifestyle changes that often cause difficulties in improving mental health. The prevalence of anxiety is much greater among people with chronic diseases. The level of anxiety experienced by individuals is influenced by psychological factors, social factors, the severity of medical conditions, and the presence of comorbid diseases. This study aims to determine the relationship between the value of left ventricular ejection fraction with the level of anxiety symptoms. This was descriptive analytic researchwith cross sectional design. The subjects in this study were heart failure patients at RSU Mitra Medika Amplas and RSU Putri Hijau Tk.II Kesdam I/BB Medan in November 2018 -January 2019 (40 patients). This research used convenience sampling techniques and data analysis using the Kruskal-Wallis test. Retrieving data through filling out questionnaires (Beck Anxiety Inventory questionnaires) and medical records. The results showed that patients who had the most anxiety were 19 respondents (47,5%), followed by patients withmild anxiety symptoms as many as 17 respondents (42.5%), then heart failure patients withsymptoms of severe anxiety were 4 respondents (10%). Heart failure patients were found tohave preserved (normal) ejection fraction 25 respondents (62,5%) and mid-range ejection fraction (moderate) 11 respondents (27,5%), reduced ejection fraction (decreased) 4 respondents (10%). The results of the Kruskal-Wallis test obtained P value is 0.011. The lower the value of the left ejection fraction, the more severe the level of anxiety symptoms felt by the patient.Keywords: Heart failure, Ejection Fraction, Anxiety